Menjadi Panembang Unggul: Strategi Peraihan Kompetensi Vokal dalam Tembang Sunda Cianjuran : (Studi Komparatif Yus Wiradiredja dan Neneng Dinar) - Budiman, Arif; Yupi Sundari; Pepep Didin Wahyudin (LP2M ISBI Bandung, 2025)
This study investiges the strategies for acquiring vocal competence in tembang sunda cianjuran through a comparative approach to two prominent panembang: Yus Wiradiredja and Neneng Dinar. Addressing the limited research that explores the learning trajectories of panembang in depth, this study employs Brinner’s theoretical framework on the stages of acquiring musical competence as the primary analytical tool. The findings indicate that while Yus followed an ideal learning path aligned with Brinner’s stages—establishing himself as a multitalented panembang with exceptional and wide-ranging musical sensitivity—Neneng also attained a high level of competence through perseverance and strong personal commitment. These results highlight the vital role of experience and consistency in shaping musical competence. The study recommends the development of panembang training models grounded in integrated technical, cultural, and reflective approaches.